Design and fabrication of S-band power amplifier for wireless sensor networks - Hoi, Tran Van; Lanh, Ngo Thi; Duong, Bach Gia (Institute of Advanced Engineering and Science, 2024)
This paper discusses the process of designing and manufacturing a wideband power amplifier operating in the S-band. To amplify a low power and broadband radio frequency signals from 2.1 GHz to 2.5 GHz, the proposed power amplifier uses a diagram of a two-stages amplification with peak offset amplification frequency 2.3 GHz. The power amplifier is designed with a center frequency difference of 2.2 GHz and 2.4 GHz respectively to achieve a bandwidth of 400 MHz. The proposed power amplifier (PA) uses RF transistor SHF-0589 using gallium arsenide heterostructure field-effect transistor (GaAs HFET) technology for high gain and low power consumption. The complete amplifier achieves power gain 21.1 dB inband 2.1-2.5 GHz and achieve maximum power gain of 22.5 dB at the frequency of 2.4 GHz; the output power rise up to 33 dBm; input reflection coefficient (S11) reaches -19.2 dB and output reflection coefficient reaches -17.2 dB. The designed amplifier circuit can be used for wireless sensor networks operating at S-band.